Retrofit Synthesis of Industrial Heat Exchanger Networks with Different Types of Heat Exchangers - Olga Arsenyeva (AIDIC Servizi S.r.l., 2021)
Heat Exchanger Network (HEN) synthesis is a powerful tool for the development of more efficient processes with high utilization of mass and energy resources. The implementation of compact heat exchangers with enhanced heat transfer into the industrial flowsheets can provide more efficient and economically feasible solutions. Plate Heat Exchanger (PHE) is one of established types of enhanced HEs. To estimate possible benefits of that kind of heat transfer enhancement, a mathematical model of PHE, which accounts for different plate types and corresponding corrugations geometry, is used. The integration of this model with the P-graph-based HEN synthesis approach allowed to create the method, which considers different types of heat exchangers. This approach enables to integrate not only conventional shell-and-tube heat exchangers, but also PHEs, which overall heat transfer coefficient is in average 2-3 times higher, during the optimization process of a new or existing HEN. The capabilities of the proposed method are presented via a case study for oil preheat train, where an existing network is retrofitted; first with shell-and-tube heat exchangers only, then with the consideration of both shell-and-tube and plate heat exchangers.